PENERAPAN THINK PAIR SHARE PADA PEMBELAJARAN IPAS : STUDI PENINGKATKAN MOTIVASI DAN PEMAHAMAN BELAJAR JUDUL ARTIKEL - Maulina, Silvia Nur; Arifin, Zainal (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was used to determine the influence of the Think Pair Share learning model on student motivation and understanding at UPTD SDN Pejagan 1 Bangkalan in science lessons. This study used a quantitative approach with a research design, namely one group pretest posttest design. The population in this study used all VB class students with a total of 23 students. The instruments used in this study were student learning comprehension questions and student learning motivation questionnaires. While the analysis test used a validity test to see the validity of an instrument, a reliability test was used to see the level of consistency of a valid instrument, a normality test to determine whether the data distribution was normal or not, a paired sample t-test was used to compare the average of two variable data from one sample group, and the Manova test was used to analyze significant differences between the average of the dependent variable and 2 or more independent variables using the SPSS application. This can be proven in the use of the TPS learning model in science lessons to improve student motivation and understanding of learning which obtained a significant value (2-tailed) of 0.0000 <0.05 which states that there is an influence of the TPS learning model on motivation and understanding.